Buckling analysis and design proposal for 2-side supported double Insulated Glass Units (IGUs) in compression. (1st August 2018) - Bedon, Chiara; Amadio, Claudio
Highlights: IGUs are largely used in buildings to realize curtain walls and enclosures. High slenderness ratios and boundaries make IGU systems susceptible to buckling. Parametric FE studies are proposed for in-plane compressed IGU panels. The structural effects of several aspects are investigated. Simplified analytical methods are assessed for the buckling verification. Abstract: Due to mainly thermal and energy potentials, Insulated Glass Units (IGUs) are largely used in modern buildings to realize curtain walls and enclosures. The typical IGU consists of two glass layers, either monolithic and/or laminated, joined together by enclosing an hermetically-sealed air (or gas) cavity between them. There, maximum stresses and deformations derive from external pressures (wind loads, etc.) or environmental/climatic loads (temperature variations, etc.). While the common IGU application involves 4-side continuous supports, novel restraint configurations are increasingly used in practice (i.e. 2-side supports, point-fixings, etc.), hence resulting in additional loading scenarios that could compromise the integrity of these systems. In this paper, following earlier research contributions, a standardized buckling approach in use for structural glass elements mainly compressed or under combined compression/bending is assessed, for the specific case of IGUs with 2-side continuous supports. Analytical and Finite Element (FE) numerical studies are reported, giving evidence of their actual performance and buckling resistance, including parametric analyses and comparisons towards simplified design formulations for both external and internal pressures.